Optimization of low-methoxyl pectin extraction from durian rinds and its physicochemical characterization - Jong, Sze Hui; Abdullah, Norazlin; Muhammad, Norhayati (Elsevier, 2023)
The current study investigates the influence of acid-heating extraction conditions on durian rind pectin yield and properties. A central composite rotatable design was employed to study the effect of extraction temperature (75 – 95 ◦C), duration (30 – 270 min), and solid-to-liquid ratio (S:L) (1:20 – 1:60 g/mL) at 0.001M H2SO4 on durian rind pectin yield, esterification degree (DE), and purity (AUA). Based on the results, pectin yield and AUA were significantly affected by extraction temperature, time, and S:L. Among them, extraction temperature was the most significant variable positively affecting the pectin yield and purity. DE was not pronouncedly influenced by extraction temperature, time, and S:L. Under the optimal extraction condition (93.3 ◦C, S:L 1:50 g/mL, 185 min), the experimental yield (12.12%) and AUA (77.21%) of the extracted pectin were in close agreement with the predicted values. The optimized pectin had DE = 18.99% and molecular weight = 42.12 kDa. The FT-IR spectrum showed that DP is rich in polygalacturonic acid. DP powders were homogenous slab-like granules with smooth surfaces and had relatively good thermal properties. Thus, durian rind is a potential source of low methoxyl pectin, which could be a capable thickener for low-calorie foods and beverages.